Potential and Limits to Diffusing Brazil's Zero Hunger Strategy in Sub-Saharan Africa: The Case of Mozambique - (:unkn) unknown (My University, 2015)
The Zero Hunger Strategy is one of Brazil's most internationally recognized experiences and is not only regarded as a relevant model in the fight against hunger and poverty, but also as a tool to promote family farming. Both international and domestic forces have led to the intent of sharing instruments of this framework, especially the Food Acquisition Programme (PAA) and School Feeding Programme (PNAE), with Sub-Saharan Africa (SSA). This article aims to discuss the potential and challenges of sharing public policy instruments for family farming between Brazil and SSA countries, with a particular focus on Mozambique. Analyzing with data collected firsthand, the article aims to address questions on the concrete impacts of Brazil's cooperation initiatives in SSA.
Keywords: African Research